2011
DOI: 10.1371/journal.pone.0022552
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Monotherapy Cannot Guarantee Euthyroidism in All Athyreotic Patients

Abstract: ContextLevothyroxine monotherapy is the treatment of choice for hypothyroid patients because peripheral T4 to T3 conversion is believed to account for the overall tissue requirement for thyroid hormones. However, there are indirect evidences that this may not be the case in all patients.ObjectiveTo evaluate in a large series of athyreotic patients whether levothyroxine monotherapy can normalize serum thyroid hormones and thyroid-pituitary feedback.DesignRetrospective study.SettingAcademic hospital.Patients1,81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
228
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(249 citation statements)
references
References 30 publications
14
228
4
3
Order By: Relevance
“…In the 1980s it was already observed that in hypothyroid patients on T4, the serum T4 required to reach a normal serum TSH, is higher than that in controls (10). This was recently confirmed in a large survey of athyreotic patients with normal TSH during T4 treatment: it showed -relative to a healthy population-a shift to the right in the distribution curve of FT4 values; FT4 levels above the upper normal limit occurred in 7.2% of the population (11). The distribution curve of FT3 was shifted to the left, with FT3 values below the lower normal limit in 15.2%.…”
Section: Introductionmentioning
confidence: 81%
“…In the 1980s it was already observed that in hypothyroid patients on T4, the serum T4 required to reach a normal serum TSH, is higher than that in controls (10). This was recently confirmed in a large survey of athyreotic patients with normal TSH during T4 treatment: it showed -relative to a healthy population-a shift to the right in the distribution curve of FT4 values; FT4 levels above the upper normal limit occurred in 7.2% of the population (11). The distribution curve of FT3 was shifted to the left, with FT3 values below the lower normal limit in 15.2%.…”
Section: Introductionmentioning
confidence: 81%
“…In our study, following total thyroidectomy, patients also received radioiodine treatment for DTC, allegedly leading to the absence of functional thyroid tissue. The absence of thyroid-derived T 3 in these patients led some authors to assume that a partial T 3 deficiency may be an issue during L-T 4 treatment after surgery (8,26). However, in a prospective study carried out in the same patients before and after thyroidectomy, no difference has been shown by comparing FT 3 levels before and after replacement T 4 dose (18).…”
Section: Discussionmentioning
confidence: 93%
“…A type 2 deiodinase polymorphism has been described in patients where a defective D2 activity was associated with an increased need for T 4 (32). However, it seems not sufficient to explain why some patients may not fully recover despite an appropriate dose of T 4 (8,33). On this ground, some studies analyzed the effects of combined T 3 /T 4 treatment in hypothyroid patients, including those who have undergone thyroidectomy (10,27,28,33,34), but mostly failed to show advantages when compared with L-T 4 therapy alone (10,25,34).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 2 more Smart Citations